Forest restoration improves habitat and water quality in tropical streams: A multiscale landscape assessment - dos Reis Oliveira, Paula C.; Gualda, Gabriel Arantes Ferreira; Rossi, Gustavo Fiedler; Camargo, António Fernando Monteiro [UNESP]; Filoso, Solange; Brancalion, Pedro Henrique; Ferraz, Silvio Frosini de Barros (Elsevier, 2025)
Forest restoration has been a common practice to safeguard water quality and stream health but it is unclear to which extent and pace forest restoration recovers stream ecosystem structure and functions. Also, stream health might be affected by the forest restoration type and the quality of the interventions. Here, we sought to evaluate the recovery of stream habitat and water quality through forest restoration in catchments dominated by pasturelands, and explored the relationship between landscape structure and stream ecosystem recovery. We sampled a total of 30 catchments during the dry season of 2023, covering six different classes (five catchment per class), based on the type and extent of forest cover: (i) all catchment area covered by native forest remnants, (ii) catchments mostly covered by old (26–37 years) restored forests, (iii) catchments mostly covered by young (5–25 years) restored forests, (iv) catchments in a pasture matrix with forest remnants around springs, (v) catchments in a pasture matrix with riparian buffers covered by pioneer vegetation (mostly herbs and shrubs), and (vi) catchments mostly covered by pastures. Data on stream water (e.g. temperature, nutrients and sediments) and habitat (e.g. substrate heterogeneity and volume of wood debris) quality were sampled and landscape metrics calculated by GIS at reach, riparian and catchment scales. In catchments covered by remnant and old restored forests, the water temperature and nutrient concentration were lower, and instream leaf banks were higher, whereas the number of large wood debris was higher in forest remnant catchments. Water temperature and ammoniacal-N correlated with Normalized Difference Vegetation Index (NDVI) at reach scale. Substrate heterogeneity and volume of woody debris correlated strongly with NDVI and proportion of forest over 38 years old at the catchment scale. This outcome shows the potential application of forest structure (NDVI) and age for monitoring the stream ecosystem benefits of forest restoration. Overall, we found a gradient of recovery of both water and habitat quality progressing from more degraded (pasture-dominated catchments, pasture-dominated with forest remnants around springs, pasture-dominated with pioneer vegetation in riparian buffers) to more conserved catchments (young forest restoration, old forest restoration and old-growth conserved forests). In conclusion, the Atlantic Forest restoration contributed to improve water and habitat quality in streams, however these benefits were dependent on forest restoration age, extension and location.
Keywords: Lag time; NDVI; Stream habitat heterogeneity; Whole catchment restoration